The order for payment process and the need for its incorporation into the Peruvian procedural system - Hidalgo Gómez , Américo (2025)
The cognition or declaratory process is currently the only mechanism that allows a creditor to claim recognition of its right, but it has significant disadvantages, such as its lengthy duration of 5 to 10 years and the high costs associated with it, even for small debts. To solve this problem, the order for payment process has been implemented in several jurisdictions, which offers a more agile procedure in which a judge can quickly recognize the creditor's right and issue an enforceable order. This process can be pure, without the need for documentary evidence, or documentary, which requires some evidence to support the claimed obligation. In case of opposition by the debtor, this must be substantiated, which may result in a declaratory proceeding to clarify the existence of the claim. The Commission for the Reform of the Code of Civil Procedure proposes two types of order for payment proceedings: one for the collection of sums of money and the other for the restitution of property. However, the procedures for recovery of possession are not considered to be compatible with the speed sought by the order for payment. For a claim to be claimable, it must be liquid, due and payable, without establishing a maximum limit on the amount. It is suggested that the burden of proof should fall on both parties in the documentary payment order process, avoiding the need to initiate a declaratory process. If there is no opposition or it is extemporaneous, the judge may conclude the process and issue a resolution with the value of an enforceable title. The purpose of this initiative is to discourage delinquency, accelerate collection processes and promote a predictable legal environment that stimulates investment